Antigenically Diverse Swine Origin H1N1 Variant Influenza Viruses Exhibit Differential Ferret Pathogenesis and Transmission Phenotypes - Pulit-Penaloza, Joanna A. (J Virol, 2018)
Influenza A(H1) viruses circulating in swine represent an emerging virus threat, as zoonotic infections occur sporadically following exposure to swine. A fatal infection caused by an H1N1 variant (H1N1v) virus was detected in a patient with reported exposure to swine and who presented with pneumonia, respiratory failure, and cardiac arrest. To understand the genetic and phenotypic characteristics of the virus, genome sequence analysis, antigenic characterization, and ferret pathogenesis and transmissibility experiments were performed. Antigenic analysis of the virus isolated from the fatal case, A/Ohio/09/2015, demonstrated significant antigenic drift away from the classical swine H1N1 variant viruses and H1N1 pandemic 2009 viruses. A substitution in the H1 hemagglutinin (G155E) was identified that likely impacted antigenicity, and reverse genetics was employed to understand the molecular mechanism of antibody escape. Reversion of the substitution to 155G, in a reverse genetics A/Ohio/09/2015 virus, showed that this residue was central to the loss of hemagglutination inhibition by ferret antisera raised against a prototypical H1N1 pandemic 2009 virus (A/California/07/2009), as well as gamma lineage classical swine H1N1 viruses, demonstrating the importance of this residue for antibody recognition of this H1 lineage. When analyzed in the ferret model, A/Ohio/09/2015 and another H1N1v virus, A/Iowa/39/2015, as well as A/California/07/2009, replicated efficiently in the respiratory tract of ferrets. The two H1N1v viruses transmitted efficiently among cohoused ferrets, but respiratory droplet transmission studies showed that A/California/07/2009 transmitted through the air more efficiently. Preexisting immunity to A/California/07/2009 did not fully protect ferrets from challenge with A/Ohio/09/2015. IMPORTANCE Human infections with classical swine influenza A(H1N1) viruses that circulate in pigs continue to occur in the United States following exposure to swine. To understand the genetic and virologic characteristics of a virus (A/Ohio/09/2015) associated with a fatal infection and a virus associated with a nonfatal infection (A/Iowa/39/2015), we performed genome sequence analysis, antigenic testing, and pathogenicity and transmission studies in a ferret model. Reverse genetics was employed to identify a single antigenic site substitution (HA G155E) responsible for antigenic variation of A/Ohio/09/2015 compared to related classical swine influenza A(H1N1) viruses. Ferrets with preexisting immunity to the pandemic A(H1N1) virus were challenged with A/Ohio/09/2015, demonstrating decreased protection. These data illustrate the potential for currently circulating swine influenza viruses to infect and cause illness in humans with preexisting immunity to H1N1 pandemic 2009 viruses and a need for ongoing risk assessment and development of candidate vaccine viruses for improved pandemic preparedness.